Dynamics and thermalization of a Bose-Einstein condensate in a Sinai-oscillator trap - Ermann, Leonardo (2016)
We study numerically the evolution of Bose-Einstein condensate in the Sinai-oscillator trap described by the Gross-Pitaevskii equation in two dimensions. In the absence of interactions, this trap mimics the properties of Sinai billiards where the classical dynamics is chaotic and the quantum evolution is described by generic properties of quantum chaos and random matrix theory. We show that, above a certain border, the nonlinear interactions between atoms lead to the emergence of dynamical thermalization which generates the statistical Bose-Einstein distribution over eigenmodes of the system without interactions. Below the thermalization border, the evolution remains quasi-integrable. Such a Sinai-oscillator trap, formed by the oscillator potential and a repulsive disk located in the vicinity of the center, had been already realized in first experiments with the Bose-Einstein condensate formation by Ketterle group in 1995 and we argue that it can form a convenient test bed for experimental investigations of dynamical of thermalization. Possible links and implications for Kolmogorov turbulence in absence of noise are also discussed.